Contextual leadership : leadership practices of successful school principals in Malaysia - Noman, Mohammad (2017)
Recent studies of the practices of successful school principals in more than twenty countries have revealed that leadership practices are more complex in nature, are heavily dependent upon the context and that there is no ‘one size fits all’ model for leadership. In the absence of similar studies conducted in Malaysia, this qualitative case study of one urban and one rural school attempts to identify the school contexts under which the two successful principals operate and how they enact their core leadership practices in response to their own contexts. The study utilizes interviews, observation notes and scanning of school documents for data collection. The principals of the two schools, three teachers, three students, three parents and one senior administrator from each of the two schools were interviewed using a semi-structured interview protocol. Both the schools were visited several times for observations, data scanning and collection of additional data from the respondents. Individual case analysis of the two schools revealed a set of seven core practices for the principal of the first school while a set of five core practices were identified for the principal of the second school. The findings also revealed specific context-based enactment of these core practices by the two principals. A subsequent in-depth cross-case analysis revealed that the core practices of the two principals fell within five distinct dimensions which are well supported by educational leadership literature. These five dimensions are (a) Strategic; (b) Pedagogic; (c) Administrative; ( d) Humanistic; (e) Collaborative. While first three dimensions are well supported by the literature on the practices of successful school principals, the humanistic and collaborative dimensions have little reference and thus are new findings. The findings are discussed in the light of current school leadership literature and have significance for the principals, policymakers and school leadership training institutes. The limitations of the study and recommendations for further research are also included.